2008
DOI: 10.1029/2008gl034288
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic effect on CO2 solubility in seawater: A possible link between geomagnetic field variations and climate

Abstract: [1] Correlations between geomagnetic-field and climate parameters have been suggested repeatedly, but possible links are controversially discussed. Here we test if weak (Earth-strength) magnetic fields can affect climatically relevant properties of seawater. We found the solubility of air in seawater to be by 15% lower under reduced magneticfield (20 mT) compared to normal field conditions (50 mT). The magnetic-field effect on CO 2 solubility is twice as large, from which we surmise that geomagnetic field vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Other studies point out other possible mechanisms which explain this connection, such as the experimental result of Pazur and Winklhofer [2008]. They focus on the effect of the geomagnetic intensity on CO2 solubility in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies point out other possible mechanisms which explain this connection, such as the experimental result of Pazur and Winklhofer [2008]. They focus on the effect of the geomagnetic intensity on CO2 solubility in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Pazur and Winklhofer [16] examined the potential source for this apparent contradiction. They found that the solubility of air in sea water was 15% lower when the average static magnetic field was 20 μT compared to the typical 50 μT.…”
Section: Introductionmentioning
confidence: 99%
“…Eastland (1938Eastland ( -2007, have and are examining the technical and environmental aspects of advantageous modification of Earth's eponymous Van Allen radiation belts, discovered by James Van Allen in 1958 (Rodger et al, 2006). It is widely postulated that Earth's geomagnetic field strength modulates surface air temperature (Usoskin, 2005), the solubility of gaseous carbon dioxide in standard seawater laboratory samples (Pazur and Winklhofer, 2008), the ocean's seawater currents (Ryskin, 2009) and measurable electromagnetic control of crustal seismic activity (Chelidze and Matcharashvili, 2003).…”
Section: Range Of Familiar Essential Artificial Rocksmentioning
confidence: 99%